Bombesin Receptor Family Activation and CNS/Neural Tumors: Review of Evidence Supporting Possible Role for Novel Targeted Therapy - Moody, Terry W.; Lee, Lingaku; Ramos-Alvarez, Irene; Iordanskaia, Tatiana; Mantey, Samuel A.; Jensen, Robert T. (Frontiers in Endocrinology, 2021)
G-protein-coupled receptors(GPCRs) are increasingly being considered as possible therapeutic targets in cancers. Activation of GPCR on tumors can have prominent growth effects and GPCRs are frequently over-/ectopic expressed on tumors and thus can be used for targeted therapy. CNS/neural tumors are receiving increasing attention using this approach. Gliomas are the most frequent primary malignant brain/CNS tumor with glioblastoma having a 10-year survival <1%; neuroblastomas the most common extracranial solid tumor in children with long-term survival<40% and medulloblastomas are less common,but one subgroup has a 5-yr survival <60 %,thus there is an increased need for more effective treatments of these tumors. The Bombesinreceptor family(BnRs) is one for the GPCRs most frequently over/ectopically expressed by common tumors,and is receiving particular attention as a possible therapeutic target in a number of tumors,particularly in prostate,breast and lung cancer. We review in this paper evidence suggesting why a similar approach in some CNS/neural tumors(gliomas,neuroblastomas,medulloblastomas) should also be considered.